1993
DOI: 10.2118/20623-pa
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Matrix Stimulation Technology

Abstract: This paper presents the results of extensive technical and statistical analyses of more than 650 matrix stimulation jobs. Seventy-eight failures were identified with absolute reliability by second stimulations successfully repeated on the same pay zones of the same wells. Only one significant parameter of the stimulation design differentiated the first failed stimulations from the second successful ones. This paper illustrates these failure/success factors and gives novel field-stimulationresponse graphs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…Moreover, after being treated with HBF 4 , Paccaloni and Mauro (1993) reported a successful 5 years production of a silt and clay damaged well caused by mud acid previously. Meanwhile, Kume et al (1999) showed that the adoption of HBF 4 in treating the Niger Delta wells caused a mixture of both positive and negative results.…”
Section: Sandstone Acidizing Treatment Fluidsmentioning
confidence: 99%
“…Moreover, after being treated with HBF 4 , Paccaloni and Mauro (1993) reported a successful 5 years production of a silt and clay damaged well caused by mud acid previously. Meanwhile, Kume et al (1999) showed that the adoption of HBF 4 in treating the Niger Delta wells caused a mixture of both positive and negative results.…”
Section: Sandstone Acidizing Treatment Fluidsmentioning
confidence: 99%
“…With this in mind, the first consideration for effective placement of a matrix treatment is rate -which is the basis of the maximum pressure differential and injection rate (MAPDIR) technique (Paccaloni and Tambini 1993). The method is often referred to as the Paccaloni method.…”
Section: Acid Placement and Diversion In The Wellbore -Matrix Acid Trmentioning
confidence: 99%
“…Matrix acidizing for both sandstone and carbonate formations is a complicated process 8,9 . The appropriate volume of acid per foot of formation should be based on formation acid response curves or other appropriate acid stimulation design criteria, the details of which are beyond the scope of this paper.…”
Section: Matrix Acidizing With Coiled Tubingmentioning
confidence: 99%
“…19, r b is the radius affected by acid injection. Paccaloni 9 suggests that a value of 4 ft should be used, which has proven to be a good assumption and is based on experience with actual jobs. Equation 19 relates q i , p wf and s. To monitor a stimulation treatment, Paccaloni constructs a graph of p ti versus q i , with s as a parameter.…”
Section: Matrix Acidizing With Coiled Tubingmentioning
confidence: 99%
See 1 more Smart Citation